Pengaruh Konseling Kelompok Rational Emotive Therapy Terhadap Self Esteem Siswa SMPN 1 Tigabinanga, Karo-Sumatera Utara - Rasita Tri Susanti Sembiring (LPPM Politeknik Pratama, 2024)
This research aims to determine the effect of group counseling services using a rational emotive therapy approach on the self-esteem of students at SMP Negeri 1 Tigabinanga. The sample in this research was 7 students. This type of research is a quasi experiment with one group pre-post test design. The data collection technique used in this research was a self-esteem questionnaire. Of the 45 items tested on 34 students, 39 items were valid and 6 were invalid. Based on the results of calculations using the Cronbach alpha formula, reliability is known to be 0.919. Data were analyzed using the Wilcoxon test to see whether there was an influence of rational emotive therapy counseling services on students' self-esteem. This can be obtained from the calculation results with the initial test score (pre-test) obtained on average = 73.1 while the post-test data obtained on average = 127.71. Data analysis using the Wilcoxon signed rank test obtained Jcount = 13 while Jtable = 2. From the table of critical values ​​J for the Wilcoxon signed rank test for n = 7, α = 0.05 in accordance with the criteria for acceptance and rejection of the hypothesis, the hypothesis is accepted if Jcount > A table where 13 > 2 means the hypothesis is accepted, meaning the hypothesis states that there is an influence of group counseling services with a rational emotive therapy approach on the self-esteem of students at SMP Negeri 1 Tigabinanga.